Internet of Things (IoT): Security, Threats and Countermeasures - Firmansyah Ibrahim; Didit Hermawan; Zulkarnaim Masyhur (Journal Software, Hardware and Information Technology, 2022)
Internet of Things (IoT) is a technology that is very popular lately and is starting to get busy in Indonesia, marked by various cellphone manufacturers building an IoT ecosystem. IoT can help connect objects such as sensors, vehicles, hospital instruments, household appliances and others. However, connecting these smart devices to the internet network causes various data security problems because internet technology and communication protocols have not been specifically designed to support IoT devices. The leakage of data security through the commercialization of IoT devices, causes privacy problems, threats of cyber-attacks, and organized crime. This paper aims to educate about how data security attacks in IoT and how to overcome them. To achieve this goal, we first discuss various well-known IoT reference models and define security in the context of IoT. Second, identify and classify various IoT attacks and threats. Third, described methods of countermeasures against IoT attacks. In the end, it provides some tips on securing IoT devices.